Information Security Management System Assessment Model by Integrating ISO 27002 and 27004 - Fajri, Khafidh Sunny Al; Harwahyu, Ruki (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2024)
The rapid development of information and communication technology has also led to a significant increase in cybercrime activities. According to the Annual Cybersecurity Monitoring Report by the National Cyber and Cryptography Agency, there were 495 million instances of traffic anomalies or attempted attacks in 2020, which rose to 1.6 billion in 2021 in Indonesia. Implementing the ISO 27001 standard for information security management system (ISMS) can help mitigate these cyber-attack attempts. However, with various levels of resources and organizational commitment, different levels of ISMS maturity can be achieved. Therefore, there is a need for an ISMS assessment model. This is crucial, considering cyber incidents such as data breaches in organizations that have implemented or are certified with ISO 27001. This research proposed a concept of ISMS assessment model by integrating ISO 27002 and 27004 to a case study (Directorate XYZ), where the guidance function of ISO 27002 is transformed into assessment parameters and ISO 27004 for measuring performance. Using this model, the score of the case study’s ISMS was found to be 53.925, which is still below the established standard of 80.